2000
DOI: 10.1046/j.1432-1327.2000.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptococcus pneumoniae 5‐enolpyruvylshikimate 3‐phosphate synthase and its activation by univalent cations

Abstract: The aroA gene (Escherichia coli nomenclature) encoding 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase from the gram-positive pathogen Streptococcus pneumoniae has been identified, cloned and overexpressed in E. coli, and the enzyme purified to homogeneity. It was shown to catalyze a reversible conversion of shikimate 3-phosphate (S3P) and phosphoenolpyruvate (PEP) to EPSP and inorganic phosphate. Activation by univalent cations was observed in the forward reaction, with NH (GLP versus PEP) up to 600-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 29 publications
(24 reference statements)
1
46
0
1
Order By: Relevance
“…Position 117 is occupied by Glu in 121 sequences and by Lys, Ser, and Arg in 106, 2, and 1 sequence, respectively. The requirement for K ϩ by 21 pyruvate kinases that have Glu at position 117 has been examined, and the activity of all of them is K ϩ -dependent (8,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The activities of eight pyruvate kinases that do not have Glu at that position have been characterized; in all cases the activity is K ϩ -independent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Position 117 is occupied by Glu in 121 sequences and by Lys, Ser, and Arg in 106, 2, and 1 sequence, respectively. The requirement for K ϩ by 21 pyruvate kinases that have Glu at position 117 has been examined, and the activity of all of them is K ϩ -dependent (8,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The activities of eight pyruvate kinases that do not have Glu at that position have been characterized; in all cases the activity is K ϩ -independent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that K ϩ changes the kinetic mechanism of rabbit muscle pyruvate kinase and is involved in the acquisition of the active conformation of the enzyme (20 (21), a water molecule, and a phosphate oxygen of phosphoenolpyruvate analogs (22), or an oxygen from the ␥-phosphate of ATP (5). For a long time, it was thought that the absolute dependence of K ϩ was a common feature to all pyruvate kinases (8,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). However, as the number of characterized enzymes increased, it became apparent that the activity of several pyruvate kinases was K ϩ -independent, for example those from Escherichia coli (Type II) (39), Phycomyces blakesleeanus (40), Corynebacterium glutamicum (41), Zymomonas mobilis (42), Thermoproteus tenax (43), Synechococcus pcc 6301 (44), Archaeoglobus fulgidus, Pyrobaculum aerophilum, Aeropyrum pernix, and Thermotoga maritima (45).…”
mentioning
confidence: 99%
“…strain CP4, isolated from a waste-fed column at a glyphosate production facility, yielded a glyphosate-resistant, kinetically efficient EPSP synthase suitable for the production of transgenic, glyphosate-tolerant crops. Other class II EPSP synthases have since been described, typically from Gram-positive bacteria, including pathogenic species such as Streptococcus pneumonia (11) and Staphylococcus aureus (12).…”
mentioning
confidence: 99%
“…The Class I enzyme found in all plants and bacteria such as Escherichia coli (Yu et al, 2015) and Salmonella enterica Typhimurium (Garg et al, 2014) is sensitive to glyphosate at low concentrations. The Class II enzyme present in bacterial species such as Pseudomonas sp strain PG2982 (Zhang et al, 2014), Agrobacterium tumefaciens strain CP4 (Heck et al, 2005), Streptococcus pneumoniae (Du et al, 2000), and Staphylococcus aureus (Priestman et al, 2005), however, can tolerate glyphosate even at high concentrations. Class I and II enzymes share less than 30% amino acid similarity (Ye et al, 2001).…”
Section: Introductionmentioning
confidence: 99%